MIGRASI TENAGA KERJA MANCANEGARA: Sebuah Kasus Dengan Pendekatan Sosiologi Ekonomi - Kartono, Drajat Tri (P2KK LIPI, 2004)
This article focuses on Research result on subject of International labour migration from Bawean Island-Indonesia to Malaysia. This Ethno economics study which is done under perspective of Economic Sociology and constructive paradigm, has prove that International economy life of Baweaness has been developed based on interrelation between local changes and the adaptation of international economy dynamic. Those interrelations have push process transformation on local and international economy life toward what so called global economy. Therefore, it is right to conclude that local economic does not change just to follow global fluid but they has significant effort to create identity and way of changes in such a way that influence the global economy changes itself.